Exchange rates and interest rates in an economy with regime shifts and sticky prices - Hans Dillén; Hans Lindberg (Sveriges Riksbank, 1998)
This paper examines how expectations of a monetary regime shift to a high inflation regime may influence interest and exchange rates in an economy with sticky prices. A country in which monetary policy lacks credibility will experience an upward bias in inflation expectations and long term interest rates, but also a weak exchange rate. Furthermore, a shift to an inflationary monetary regime will be accompanied by a jump in the exchange rate. Expectations of such a jump will put an upward pressure on short-term interest rates in the economy. The effects on prices and financial variables are formalized as regime shift premia that are explicitly characterized.
Keywords: 330